Improved in vivo anti-tumor effects of IgA-Her2 antibodies through half-life extension and serum exposure enhancement by FcRn targeting. Issue 1 (2nd January 2016) - Meyer, Saskia; Nederend, Maaike; Jansen, J.H. Marco; Reiding, Karli R.; Jacobino, Shamir R.; Meeldijk, Jan; Bovenschen, Niels; Wuhrer, Manfred; Valerius, Thomas; Ubink, Ruud; Boross, Peter; Rouwendal, Gerard; et al.
Abstract : Antibody therapy is a validated treatment approach for several malignancies. All currently clinically applied therapeutic antibodies (Abs) are of the IgG isotype. However, not all patients respond to this therapy and relapses can occur. IgA represents an alternative isotype for antibody therapy that engages FcαRI expressing myeloid effector cells, such as neutrophils and monocytes. IgA Abs have been shown to effectively kill tumor cells both in vitro and in vivo. However, due to the short half-life of IgA Abs in mice, daily injections are required to reach an effect comparable to IgG Abs. The relatively long half-life of IgG Abs and serum albumin arises from their capability of interacting with the neonatal Fc receptor (FcRn). As IgA Abs lack a binding site for FcRn, we generated IgA Abs with the variable regions of the Her2-specific Ab trastuzumab and attached an albumin-binding domain (ABD) to the heavy or light chain (HCABD /LCABD ) to extend their serum half-life. These modified Abs were able to bind albumin from different species in vitro. Furthermore, tumor cell lysis of IgA-Her2-LCABD Abs in vitro was similar to unmodified IgA-Her2 Abs. Pharmacokinetic studies in mice revealed that the serum exposure and half-life of the modified IgA-Her2 Abs was extended. In a xenograft mouse model, the modified IgA1 Abs exhibited a slightly, but significantly, improved anti-tumor response compared to the unmodified Ab. In conclusion, empowering IgA Abs with albumin-binding capacity results in in vitro and in vivo functional Abs with an enhanced exposure and prolonged half-life.